A bibliometric portrait of the Brazilian scientific production on Technology and Innovation Management in the period 2001-2011 - de Andrade Júnior, Pedro Paulo; Ceranto, Fabrício Alexandre Alves (Revista de Administração da UFSM, 2013)
The present paper had as objective to map the Brazilian scientific production on Technology and Innovation Management (GTI) in the period 2001-2011, in view of identifying (i) the total number to published articles, as well as the number in each of the years; (ii, iii, iv and v) journals, authors, institutions and states that have most published articles. This study is justified because literature says that GTI studies may help countries to achieve higher levels of entrepreneurial innovation and technology performance, since these studies are absorbed by the companies and innovation incentive agencies. Thus, knowing how scientific production has been occurring in the country is an aspect of relevance for the governmental agencies that incentive entrepreneurial innovation in the country. This knowledge is also important for researchers, due to several other reasons. The mapping was made through a bibliometric method. The results show that the Brazilian scientific production on GTI is not very large, in terms of number, and it is too concentrated (in terms of institutions and territory), factors that certainly hinder the dissemination and rooting of an innovation culture in Brazil. From the results, it was also possible to verify that in the locations where GTI scientific production is more strongly concentrated the levels of technological, economic and social development are quite higher than the national average, which elucidates the mentioned relevance of the GTI scientific production.